(3OYGA GdeZfj GdPj jbQC HYO bQGAI GdSjajs
(3ChdgG (B:s
(3gPG OYGA GdeZfj GdPj jbQC HYO bQGAI GdSjaj GdeGfY Hc CSJZjK aCZKfj s
(3BNQgG (B:s
(3hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO hSde JSdjekG cKjQkG Edi jhe GdOjf GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3HBNQg aGFOIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdQHGW (B- (3GdeZQH (B(1370 (3O(B) s
Keywords: (3GdMQha h GdChaGbs